The Effect of Teacher Creativity on Students' Learning Interest in Islamic Education at Elementary School - Savira Nur Azzahro; Didit Darmawan (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
In elementary school classrooms, a decline in learning motivation among some students is still observed, often linked to the tendency to use repetitive teaching methods and the limited variety of instructional media employed. Based on this reality, this study aims to examine the relationship between teacher creativity and student learning motivation at the elementary school level. This research employs a qualitative approach with a literature review design, involving the search and analysis of scientific articles, journals, and relevant prior research findings. The collected data were then processed descriptively to identify relational trends among the variables under study. The synthesis results indicate that teacher creativity plays a crucial role in strengthening students’ interest in learning, particularly through the diversification of learning strategies, the use of more innovative media, and the ability to foster a classroom environment that is more supportive and conducive from a psychopedagogical perspective. A number of empirical findings also affirm the existence of a positive relationship between teacher creativity and learning interest, although certain external factors still contribute to the dynamics of learning engagement. More creative teachers tend to be able to orchestrate participation, increase learning motivation, and foster students’ academic responsibility more effectively. Thus, teachers’ creativity can be viewed as an essential pedagogical factor in optimizing students’ interest in learning and the overall effectiveness of instruction. Consequently, strengthening teachers’ creative capacities is a strategic aspect of improving the quality of basic education.